Economic costs related to foodborne disease in Burkina Faso and Ethiopia in 2017 - Wagenberg, C.P.A. van; Havelaar, A.H. (Frontiers Media, 2023)
Introduction: Foodborne diseases (FBD) are a significant problem in low- and middle-income countries, especially in Africa. Country-specific estimates of the economic costs related to FBD caused by different hazards in different food products can inform decision makers about this problem’s magnitude. This aids policy makers in prioritising actions to mitigate risks and prevent illness. Although estimates exist for many high-income countries, they are lacking for African countries.